Facial acne causes stigmatization among adolescents: A cross‐sectional study - Szepietowska, Marta; Dąbrowska, Alicja; Nowak, Bernadetta; Skinderowicz, Katarzyna; Wilczyński, Bartosz; Krajewski, Piotr K.; Jankowska‐Konsur, Alina (Journal of cosmetic dermatology, 2022)
Background Stigmatization is defined as a discrediting mark which sets the person from others and hindering interpersonal relationships. Literature data on stigma in acne subjects are scarce. Aims This study was undertaken to assess feelings of stigmatization in adolescents with facial acne. Material/Methods The study was performed on 730 high‐school students aged 15 to 19 years with the mean age of 17.05 ± 1.18 years. Self‐reported acne was found in 74.9% of subjects. The severity of acne was self‐assessed with the standardized color images based on Investigators Global Assessment (IGA). Stigmatization was studied with 6‐Item Stigmatization Scale (6‐ISS) and Perceived Stigmatization Questionnaire (PSQ). Additionally, quality of life (QoL) was evaluated with Dermatology Life Quality Index (DLQI). Results 58% of adolescents with acne presented with feelings of stigmatization. Within the acne population, stigmatization was significantly more common in females than in males (p < 0.001). The mean level of stigmatization according to 6‐ISS was significantly higher in acne sufferers than in those free from acne (1.68 ± 2.42 points and 0.55 ± 1.50 points, respectively; p < 0.001). Feelings of stigmatization were significantly more pronounced by females than males (p < 0.001). Staring at the skin and the fact that others are not attracted to person due to skin lesions were main problems raised by the study participants with acne. 6‐ISS scores correlated with acne severity (r = 0.278; p < 0.001) and both 6‐ISS and PSQ scores with QoL impairment (r = 0.530; p < 0.001 and r = 0.341; p < 0.001, respectively). Conclusions Facial acne is a highly stigmatized skin disease and requires a holistic therapeutic approach.